Dynamics of loan delinquency by SME owners in Uganda - Busingye, John (Advances in Social Sciences Research Journal, 2019)
The study mainly set out to investigate the factors that influence loan delinquency bySME owners in Uganda. SME ownersin Mbarara Municipality, South West Uganda provided conceptual setting of the study. This paper contributes to the body of knowledge by determining the local business context influencing loan delinquency among SME owners. The study fixated on thefactors that influence loan delinquency by SME owners in Uganda with focus on what SACCOs put into consideration in order to categorize an SME as suitable for micro-lending. The study engaged descriptive research design, where 20 questionnaires were administered to SME owners and detailed discussions of the questions conducted with 6 key informants in the SME sector. The study was grounded on David McClelland’s Acquired Needs theory and the Rational Choice theory in helping to understand the subject under investigation. The study further adopted Krejcie and Morgan’s (1970) sample size determination methodology to select the respondents. Data was analysed using SPSS version 20, thematic and content analysis. The study findings show that majority of the respondents were male with secondary level of education, majority of the SME entities had been in operation for six years and above and their ability to manage loans was boosted by education, skills and experience. While the majority of the SME owners are accessing and utilizing loan services from the SACCOs, more than half of them have ever been in delinquency over their loan contract. The study recommends that the SME owners learn how to plough back their profits into their business, conduct sound business research so as to increase their operational capital and skills in order to expand and grow their projects. The study concluded that the SME industry is a fertile ground for investment for Uganda, SME owners, and SACCOs.